2013
DOI: 10.1051/0004-6361/201321374
|View full text |Cite
|
Sign up to set email alerts
|

Is MgIIλ2800 a reliable virial broadening estimator for quasars?

Abstract: Context. Broad Mgiiλ2800 and Hβ lines have emerged as the most reliable virial estimators of the black hole mass in quasars. Which is more reliable? Part of the challenge centers on comparing Mgiiλ2800 and Hβ line profiles in order to improve the ±1 dex M BH uncertainties inherent in single-epoch FWHM measures from noisy spectra. Aims. We compare Mgiiλ2800 and Hβ profile measures in the same sources and especially FWHM measures that provide the virial broadening estimator. Methods. We identify 680 bright Sloan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
165
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 88 publications
(181 citation statements)
references
References 112 publications
(208 reference statements)
14
165
2
Order By: Relevance
“…More expedient in the analysis of large ensembles of quasar spectra is to estimate the quasar redshift from lowionization emission lines (typically Hβ or Hα narrow component, the partially resolved [OII]λ3727 doublet, or [NII]λ6548,6583). There are several caveats also with this approach but these lines are customarily sharply peaked and, with good S/N ( > ∼ 20), make possible the definition of a conventional quasar rest frame with a precision ≈ ±50 km s −1 (Marziani et al 2013). Progressing to high redshift is not easy.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…More expedient in the analysis of large ensembles of quasar spectra is to estimate the quasar redshift from lowionization emission lines (typically Hβ or Hα narrow component, the partially resolved [OII]λ3727 doublet, or [NII]λ6548,6583). There are several caveats also with this approach but these lines are customarily sharply peaked and, with good S/N ( > ∼ 20), make possible the definition of a conventional quasar rest frame with a precision ≈ ±50 km s −1 (Marziani et al 2013). Progressing to high redshift is not easy.…”
mentioning
confidence: 99%
“…The HE spectra were modeled with a χ 2 minimization procedure using the routine specfit implemented in the IRAF package (Kriss 1994). The details of the analysis techniques have been described elsewhere (Marziani et al 2009(Marziani et al , 2013Negrete et al 2014). Here we recall that the main elements of the multicomponent fits are continuum shape (a power-law), Feii emission template, a Lorentzian function to represent Pop.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Note here that the literature in the field presents comparisons on the use of the optical and the UV lines, like Hβ and Mg II, as virial estimators of the M BH in AGN, pointing out that in some cases Mg II is more reliable as M BH estimator then Hβ (e.g., Marziani et al, 2013, and references therein). However, it has been shown that the Mg II wings are emitted from the weakly gravitationally bounded gas (see Kovačević-Dojčinović and Popović, 2015;Jonić et al, 2016), i.e., the assumption of virialization may be problem in using Mg II line as the BH mass estimator.…”
Section: Testing the Virialization Of The Broad Hβ And Mg II Linesmentioning
confidence: 96%
“…(Marziani et al 2013). These templates give systematic residuals at 2950 Å due to the absence of Fe I emission in the model (see Marziani et al, for the discussion), but our fits did not extend to such wavelengths.…”
Section: Mean Spectrummentioning
confidence: 99%